2017
DOI: 10.1371/journal.pone.0182454
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral denervation participates in heterotopic ossification in a spinal cord injury model

Abstract: We previously reported the development of a new acquired neurogenic HO (NHO) mouse model, combining spinal cord transection (SCI) and chemical muscle injury. Pathological mechanisms responsible for ectopic osteogenesis after central neurological damage are still to be elucidated. In this study, we first hypothesized that peripheral nervous system (PNS) might convey pathological signals from injured spinal cord to muscles in NHO mouse model. Secondly, we sought to determine whether SCI could lead to intramuscul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
(45 reference statements)
0
8
1
Order By: Relevance
“…Three amplifications, consisted of an initial denaturation cycle at 95 °C for 2 min, followed by 40 cycles of 20 s at 95 °C (denaturation), 20 s at optimal annealing temperature, and 20 s at 72 °C (extension), were performed for each primer, followed by a melt curve analysis. Threshold cycle for each target gene of interest was normalised to the housekeeping gene 18S (annealing temperature, 55.7 °C), which has been extensively used in muscle [ 18 , 19 , 20 ], and analysed using the delta-delta (2 −ΔΔCt ) method [ 21 ]. The sequences and annealing temperature of all mitochondrial- and ER stress pathway-associated primers used are provided in Table 1 and Table 2 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Three amplifications, consisted of an initial denaturation cycle at 95 °C for 2 min, followed by 40 cycles of 20 s at 95 °C (denaturation), 20 s at optimal annealing temperature, and 20 s at 72 °C (extension), were performed for each primer, followed by a melt curve analysis. Threshold cycle for each target gene of interest was normalised to the housekeeping gene 18S (annealing temperature, 55.7 °C), which has been extensively used in muscle [ 18 , 19 , 20 ], and analysed using the delta-delta (2 −ΔΔCt ) method [ 21 ]. The sequences and annealing temperature of all mitochondrial- and ER stress pathway-associated primers used are provided in Table 1 and Table 2 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…[356] Although the mechanism of heterotopic ossification is still unclear, some studies have identified a close connection between the nervous system and the abnormally strong ossification ability. [357][358][359][360] When stimulation from the nervous system is applied under suitable conditions, the mediating pathway from nerve to bone is opened. Solving this riddle may offer a solution to the problem of insufficient bone formation in the repair of large clinical wounds.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…30 NHO animal studies have demonstrated that peripheral denervation increased HO volume on the original SCI NHO model and peripheral denervation alone without SCI could also induce HO in about 50% of mice with local muscular injury. 31 Risk factors for NHO include artificial ventilation, immobilization and muscular spasticity. 26 Specifically, artificial ventilation alters blood homeostasis of electrolytes and acid-base balance, both of which will affect osteogenesis.…”
Section: Neurog Eni C Homentioning
confidence: 99%
“…32 This could possibly be explained by the fact that BTA injection equals to a denervation model, and peripheral denervation has been previously shown to enhance NHO. 31 The aetiology of NHO is incompletely understood. A general hypothesis for NHO pathogenesis involves the release of osteogenic humoral factors following the breakdown of blood-brain barrier.…”
Section: Neurog Eni C Homentioning
confidence: 99%